PROFESSIONAL IDENTITY OF HIGH SCHOOL ENGLISH TEACHERS IN ISLAMIC BOARDING SCHOOLS - Abdul Hamid; Bradhiansyah Tri Suryanto (Pascasarjana Universitas Al-Qolam Malang, 2026)
This study explores how an English teacher negotiates professional identity in a pesantren-based secondary school. It focuses on the institutional, cultural-religious, and personal factors that shape teacher identity, as well as the strategies used to align English language teaching with pesantren values. This research employed a qualitative case study design at Madrasah Aliyah Pondok Pesantren Zainul Bahar, Wringin, Bondowoso, East Java. Data were collected through semi-structured interviews, classroom observation, and document analysis, and were analyzed using thematic analysis. The findings show that the teacher’s professional identity is dynamic, contextual, and hybrid. The teacher maintained English learning objectives while adapting materials, filtering culturally sensitive topics, integrating Islamic values, using code-switching, and managing classroom interaction through adab-based practices. The study concludes that English teacher identity in a pesantren context is constructed through continuous negotiation between academic goals and religious-cultural expectations. These findings highlight the need for culturally responsive English pedagogy in Islamic educational settings.